Power law distribution in education: University entrance examination - Gupta, Hari M. [UNESP]; Campanha, José R. [UNESP]; Prado, Fernando D. [UNESP] (World Scientific Publishing, 2000)
We studied the statistical distribution of candidate's performance which is measured through their marks in university entrance examination (Vestibular) of UNESP (Universidade Estadual Paulista) for years 1998, 1999, and 2000. All students are divided in three groups: Physical, Biological and Humanities. We paid special attention to the examination of Portuguese language which is common for all and examinations for the particular area. We observed long ubiquitous power law tails in Physical and Biological sciences. This indicate the presence of strong positive feedback in sciences. We are able to explain completely these statistical distributions through Gradually Truncated Power law distributions which we developed recently to explain statistical behavior of financial market. The statistical distribution in case of Portuguese language and humanities is close to normal distribution. We discuss the possible reason for this peculiar behavior.
Keywords: Gradually Truncated Lèvy Flight; Power-Law Distributions; University Entrance Examination